Milk free of A1 β-casein supports superior gains in cognition and quality of life, relative to conventional milk, in older adults with mild cognitive impairment - Keming Zhang; Jianqin Sun; Mingming Han; Yingfei Diao; Yan Xia; Congqing Yang; Stephen R. Robinson (The Journal of Nutrition, Health and Aging)
Objectives: To determine whether the regular consumption of milk free from A1 β-casein (A1PF milk) improves cognitive performance to a greater extent than conventional milk, and if so, whether such improvements are associated with an increase in the serum titres of reduced glutathione (GSH). Design: A multi-centre, double-blind, randomised controlled trial with two parallel arms, conducted from 7 March 2023 to 13 October 2023. Setting: Two hospitals in Tianjin, China. Participants: Volunteers (N = 96) diagnosed with mild cognitive impairment (MCI) and aged between 65 and 75 years. Intervention: A1PF skim milk powder or conventional skim milk powder, diluted into liquid form (200 mL) and consumed twice daily for 90 days. Measurements: The primary outcomes were cognitive performance (assessed with the Subtle Cognitive Impairment Test [SCIT]) and serum titres of GSH. Secondary outcomes included performance on two other cognitive tests, serum levels of 25-hydroxyvitamin D3, subjective quality of life (QoL), muscle strength (hand grip scale), faecal and blood inflammatory markers. Results: Data from 91 participants were analysed (A1PF milk group: n = 45; conventional milk group: n = 46). A1PF milk improved performance on all three cognitive tests to a greater extent than conventional milk; however, this improvement was not associated with an increase in serum GSH. When compared with conventional milk, A1PF milk resulted in higher increases in serum levels of 25-hydroxyvitamin D3, greater subjective improvements in QoL and improved left hand grip strength. There were no between-group differences in inflammatory markers, calcium absorption or bone density markers. Conclusion: Daily intake of A1PF milk for 90 days significantly improved cognition, QoL and muscle strength in a sample of older people with MCI. While these outcomes appear to be linked to increased serum titres of 25-hydroxyvitamin D3, further investigations are needed to confirm this association. Clinical trial registration: NCT05741047 (clinicaltrials.gov).